x2+\(9\sqrt{x}\)+14
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
ĐKXĐ: \(x\ge-5\)
\(\Leftrightarrow\left(x+7\right)^2-2\left(x+7\right)\sqrt{x+5}+x+5-16=0\)
\(\Leftrightarrow\left(x+7-\sqrt{x+5}\right)^2-16=0\)
\(\Leftrightarrow\left(x+7-\sqrt{x+5}-4\right)\left(x+7-\sqrt{x+5}+4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}\sqrt{x+5}=x+3\left(x\ge-3\right)\\\sqrt{x+5}=x+11\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x+5=x^2+6x+9\\x+5=x^2+22x+121\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x^2+5x+4=0\\x^2+21x+116=0\left(vn\right)\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=-4< -3\left(l\right)\end{matrix}\right.\)
\(a,ĐK:x\ge1\\ PT\Leftrightarrow\sqrt{x-1}+6\sqrt{x-1}=14\\ \Leftrightarrow7\sqrt{x-1}=14\\ \Leftrightarrow\sqrt{x-1}=2\Leftrightarrow x-1=4\\ \Leftrightarrow x=5\left(tm\right)\\ b,ĐK:-2\le x\le2\\ PT\Leftrightarrow\sqrt{2-x}\left(1-\sqrt{2+x}\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}2-x=0\\2+x=1\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=2\left(tm\right)\\x=-1\left(tm\right)\end{matrix}\right.\)
a) ĐKXĐ: \(x\ge1\)
\(pt\Leftrightarrow\sqrt{x-1}+6\sqrt{x-1}=14\)
\(\Leftrightarrow7\sqrt{x-1}=14\Leftrightarrow\sqrt{x-1}=2\)
\(\Leftrightarrow x-1=4\Leftrightarrow x=5\left(tm\right)\)
b) ĐKXĐ: \(-2\le x\le2\)
\(pt\Leftrightarrow\sqrt{2-x}-\sqrt{\left(2-x\right)\left(x+2\right)}=0\)
\(\Leftrightarrow\sqrt{2-x}\left(1-\sqrt{x+2}\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}2-x=0\\x+2=1\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x=2\left(tm\right)\\x=-1\left(tm\right)\end{matrix}\right.\)
2: \(\Leftrightarrow\left(x^2+x\right)^2-5\left(x^2+x\right)-6=0\)
\(\Leftrightarrow x^2+x-6=0\)
=>(x+3)(x-2)=0
=>x=-3 hoặc x=2
5: \(\Leftrightarrow\left(x+2\right)\left(x-1\right)\left(x+1\right)=0\)
hay \(x\in\left\{-2;1;-1\right\}\)
\(A=\sqrt[3]{2^3+3.2^2.\sqrt{2}+3.2.\sqrt{2}^2+\sqrt{2}^3}+\sqrt[3]{\sqrt{2}^3-3.\sqrt{2}^2.2+3.\sqrt{2}.2^2-2^3}\)
\(A=\sqrt[3]{\left(2+\sqrt{2}\right)^3}+\sqrt[3]{\left(\sqrt{2}-2\right)^3}\)
\(A=2+\sqrt{2}+\sqrt{2}-2=2\sqrt{2}\)
\(X=\sqrt[3]{1+\frac{\sqrt{84}}{9}}+\sqrt[3]{1-\frac{\sqrt{84}}{9}}\)
\(\Rightarrow X^3=\left(\sqrt[3]{1+\frac{\sqrt{84}}{9}}+\sqrt[3]{1-\frac{\sqrt{84}}{9}}\right)^3\)
\(\Rightarrow X^3=2+3\sqrt[3]{1-\frac{84}{81}}\left(\sqrt[3]{1+\frac{\sqrt{84}}{9}}+\sqrt[3]{1-\frac{\sqrt{84}}{9}}\right)\)
\(\Rightarrow X^3=2-3\sqrt[3]{\frac{1}{27}}.X\)
\(\Rightarrow X^3=2-X\)
\(\Rightarrow X^3+X-2=0\)
\(\Rightarrow\left(X-1\right)\left(X^2+2X+2\right)=0\)
\(\Rightarrow X=1\) (do \(X^2+2X+2=\left(X+1\right)^2+1>0\) \(\forall X\))
c: \(x^2-6\sqrt{x^2+5}+x=2\sqrt{x-1}-14\)
=>\(x^2-4-6\left(\sqrt{x^2+5}-3\right)+x-2-2\sqrt{x-1}+2=0\)
=>\(\left(x-2\right)\left(x+2\right)-6\cdot\dfrac{x^2+5-9}{\sqrt{x^2+5}+3}+\left(x-2\right)-2\cdot\dfrac{x-1-1}{\sqrt{x-1}+1}=0\)
=>\(\left(x-2\right)\left(x+2\right)-\dfrac{6}{\sqrt{x^2+5}+3}\cdot\left(x-2\right)\left(x+2\right)+\left(x-2\right)-2\cdot\dfrac{x-2}{\sqrt{x-1}+1}=0\)
=>\(\left(x-2\right)\left[\left(x+2\right)-\dfrac{6}{\sqrt{x^2+5}+3}\cdot\left(x+2\right)+1-\dfrac{2}{\sqrt{x-1}+1}\right]=0\)
=>x-2=0
=>x=2
d: \(x^2-\sqrt{\left(x^2-8\right)\left(x-2\right)}+x=\sqrt{x^2-8}+\sqrt{x-2}+9\)
=>\(x^2-9-\sqrt{\left(x^2-8\right)\left(x-2\right)}+x-\sqrt{x^2-8}-\sqrt{x-2}=0\)
=>\(\Leftrightarrow\left(x-3\right)\left(x+3\right)-\sqrt{x^3-2x^2-8x+16}+x-3+1-\sqrt{x^2-8}+2-\sqrt{x-2}=0\)
=>\(\left(x-3\right)\left(x+3\right)+\left(x-3\right)-\sqrt{x^3-2x^2-8x+16}+1+\dfrac{1-x^2+8}{1+\sqrt{x^2-8}}+1-\sqrt{x-2}=0\)
=>\(\left(x-3\right)\left(x+4\right)-\dfrac{x^3-2x^2-8x+16-1}{\sqrt{x^3-2x^2-8x+16}+1}-\dfrac{\left(x-3\right)\left(x+3\right)}{\sqrt{x^2-8}+1}+\dfrac{1-x+2}{1+\sqrt{x-2}}=0\)
=>\(\left(x-3\right)\left(x+4\right)-\dfrac{x^3-2x^2-8x+15}{\sqrt{x^3-2x^2-8x+16}+1}-\dfrac{\left(x-3\right)\left(x+3\right)}{\sqrt{x^2-8}+1}-\dfrac{x-3}{1+\sqrt{x-2}}=0\)
\(\Leftrightarrow\left(x-3\right)\left(x+4\right)-\dfrac{\left(x-3\right)\left(x^2+x-5\right)}{\sqrt{x^3-2x^2-8x+16}+1}-\dfrac{\left(x-3\right)\left(x+3\right)}{\sqrt{x^2-8}+1}-\dfrac{x-3}{1+\sqrt{x-2}}=0\)
\(\Leftrightarrow\left(x-3\right)\left[\left(x+4\right)-\dfrac{x^2+x-5}{\sqrt{x^3-2x^2-8x+16}+1}-\dfrac{x+3}{\sqrt{x^2-8}+1}-\dfrac{1}{\sqrt{x-2}+1}\right]=0\)
=>x-3=0
=>x=3
h: \(\sqrt{18x}+\sqrt{32x}-14=0\)
\(\Leftrightarrow7\sqrt{2x}=14\)
hay x=2